Effects of a multidisciplinary team-led school-based human papillomavirus vaccination health-promotion programme on improving vaccine acceptance and uptake among female adolescents: A cluster randomized controlled trial. Issue 37 (11th September 2020) - Chau, Janita Pak Chun; Lo, Suzanne Hoi Shan; Choi, Kai Chow; Lee, Vivian Wing Yan; Lui, Grace Chung Yan; Chan, Kam Ming; Lau, Alexander Yuk Lun
Abstract: Introduction: Evidence has consistently shown the high efficacy of human papillomavirus (HPV) vaccines in preventing cervical cancers. However, the HPV vaccine uptake rate in Hong Kong is very low. We will develop and evaluate an innovative, theory-based multidisciplinary team-led school-based HPV vaccination health-promotion program (MDL-SHPVP), engaging female adolescents, parents/guardians, and secondary school personnel in multicomponent educational strategies and interactive discussions. Methods and analysis: A cluster randomized controlled trial is proposed. We will recruit 2520 female adolescents and their parents/guardians from 18 secondary day schools. The MDL-SHPVP is underpinned by the Health Belief Model and Precaution Adoption Process Model. Multicomponent interventions will be offered, including education sessions with small group dialogues with a registered nurse and trained healthcare and lay volunteers, and educational computer games. A team of volunteers will be established to raise HPV, cervical cancer, and HPV vaccine awareness. Outcomes include adolescents' uptake of the HPV vaccine, adolescents' intention to receive HPV vaccination, vaccine acceptance among parents/guardians, and parents'/guardians' and adolescents' HPV knowledge, attitudes, and beliefs. Data will be collected at baseline, 1 month, and 1 year after intervention. The generalized estimating equations analysis will be used for comparing the outcomes between the 2 groups. Ethics and dissemination: Ethical approval was obtained from the Joint Chinese University of Hong Kong-New Territories East Cluster Clinical Research Ethics Committee (Ref. no.: 2019.055). We will disseminate the study findings via peer-reviewed publications and presentations at relevant events and international and local conferences. Trial registration number: ClinicalTrials.gov NCT04438291